Bringing the war home : the Weather Underground, the Red Army Faction, and revolutionary violence in the sixties and seventies - Varon, Jeremy, 1969- (University of California Press, 2004)
In this first comprehensive comparison of left-wing violence in the United States and West Germany, Jeremy Varon focuses on America's Weather Underground and Germany's Red Army Faction to consider how and why young, middle-class radicals in prosperous democratic societies turned to armed struggle in efforts to overthrow their states.